Cover Feature: Reconstitution and Coupling of DNA Replication and Segregation in a Biomimetic System (ChemBioChem 20/2019). (17th October 2019) - Hürtgen, Daniel; Mascarenhas, Judita; Heymann, Michael; Murray, Seán M.; Schwille, Petra; Sourjik, Victor
Abstract : The replication and segregation of genetic material constitutes an essential feature for the design of a minimal synthetic cell. As depicted on the cover, we used T7 polymerase and the plasmid‐derived ParMRC segregation system to establish these processes in vitro. These processes were incorporated into biomimetic compartments providing an enclosed reaction space. We further show that DNA replication and segregation could be coupled by using the condensed state of DNA nanoparticles, which emerge as a result of DNA replication. Overall, this work demonstrates an important step towards the development of a fully functional minimal cell. More information can be found in the full paper by D. Hürtgen, V. Sourjik, et al. on page 2633 in Issue 20, 2019 (DOI: 10.1002/cbic.201900299 ).